2022
DOI: 10.1097/cmr.0000000000000833
|View full text |Cite
|
Sign up to set email alerts
|

Survival in adult patients with BRAFV600 mutation-positive advanced melanoma: a noninterventional ambispective study of patients with cobimetinib combined with vemurafenib during the French early access program: MELANIS study

Abstract: Cobimetinib combined with vemurafenib was available in France in 2015 through a ‘Temporary Authorization for Use’ program (TAU, preapproval access pending its marketing on 2016) for patients with v-raf murine sarcoma viral oncogene homolog B1-mutant advanced melanoma. This study aimed to provide real-world outcomes in patients previously registered in this TAU. This noninterventional, ambispective, multicentre French study, conducted in patients previously registered in TAU, aimed to estimate overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Our data confirmed previous observations from the pooled analysis of BRIM-2, BRIM-3, BRIM-7, and coBRIM clinical trials on the prognostic significance of LDH level and performance status (ECOG) for OS and data from the real-world MELANIS study, where in addition to the above-mentioned, OS was influenced by the presence of brain metastases [ 12 , 18 ]. Performing multivariate Cox analysis, we identified clinical baseline parameters which predict therapy outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our data confirmed previous observations from the pooled analysis of BRIM-2, BRIM-3, BRIM-7, and coBRIM clinical trials on the prognostic significance of LDH level and performance status (ECOG) for OS and data from the real-world MELANIS study, where in addition to the above-mentioned, OS was influenced by the presence of brain metastases [ 12 , 18 ]. Performing multivariate Cox analysis, we identified clinical baseline parameters which predict therapy outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…The mOS of non-co-BRIM-like patients was shorter than that of co-BRIM-like patients (14.7 months vs 25.4 months, respectively), but there were practically no differences in mPFS (7.2 months vs 7.7 months). However, the small size of the co-BRIM-like group (47 patients) and the heterogeneity of the population (51.4% received previous systemic treatment) make it impossible to clearly interpret the results of this study [ 12 ]. Likewise, Ismail et al, in a large analysis (435 patients) conducted on a real-world Dutch population treated with first-line BRAFi and MEKi (D+T 86% and V + C 14%), divided patients according to the inclusion criteria for the COMBI-d study into trial eligible and ineligible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For reports on dabrafenib plus trametinib, we identified a French phase IIIB early access program (EAP) in 856 patients [ 23 ], a Dutch population study using data from a prospectively planned registry describing outcomes of 435 first-line patients [ 24 ], and a small Japanese post-marketing surveillance study [ 25 ]. For the combination of vemurafenib plus cobimetinib, only one completely published non-retrospective real-world study report from France was identified [ 26 ]. Apart from these prospective non-interventional studies, a number of retrospective studies and case series were published; however, due to the known constraints of retrospective studies, we refer in this discussion to the few published real-world and the previously cited confirmative trials on BRAF/MEK inhibition.…”
Section: Discussionmentioning
confidence: 99%